Randomized, Double-Blind, Placebo-Controlled Parallel Clinical Trial Assessing the Effect of Fructooligosaccharides in Infants with Constipation - Souza, Daniela da Silva; Tahan, Soraia; Weber, Thabata Koester [UNESP]; Araujo-Filho, Humberto Bezerra de; Morais, Mauro Batista de (Mdpi, 2018)
Constipation often begins in the first year of life. The aim of this study was to assess the effect of fructooligosaccharides (FOS) in the treatment of infants with constipation. This randomized, double-blind, placebo-controlled clinical trial included infants with constipation who were randomly assigned to one of two parallel groups: FOS or placebo. Either the FOS supplement or the placebo was added to the infant formula. Thirty-six infants completed the 4-week intervention. Therapeutic success occurred in 83.3% of the FOS group infants and in 55.6% of the control group infants (p = 0.073; one-tailed test). Compared with the control group, the FOS group exhibited a higher frequency of softer stools (p = 0.035) and fewer episodes of straining and/or difficulty passing stools (p = 0.041). At the end of the intervention, the mouth-to-anus transit time was shorter (22.4 and 24.5 h, p = 0.035), and the Bifidobacterium sp. count was higher (p = 0.006) in the FOS group. In conclusion, the use of FOS in infants with constipation was associated with significant improvement in symptoms, but the results showed no statistical significance regarding the success of the therapy compared with the control group. FOS was associated with reduced bowel transit time and higher counts of the genus Bifidobacterium in the stool.
Keywords: constipation; prebiotic; intestinal transit time; infant; Bifidobacterium